Structural and regulatory diversity shape HLA-C protein expression levels - Kaur, G; Gras, S; Mobbs, J; Vivian, J; Cortes, A; Barber, T; Kuttikkatte, S; Jensen, L; Attfield, K; Dendrou, C; Carrington, M; McVean, G; et al. (Springer Nature, 2017)
Expression of HLA-C varies widely across individuals in an allele-specific manner. This variation in expression can influence efficacy of the immune response, as shown for infectious and autoimmune diseases. MicroRNA binding partially influences differential HLA-C expression, but the additional contributing factors have remained undetermined. Here we use functional and structural analyses to demonstrate that HLA-C expression is modulated not just at the RNA level, but also at the protein level. Specifically, we show that variation in exons 2 and 3, which encode the α1/α2 domains, drives differential expression of HLA-C allomorphs at the cell surface by influencing the structure of the peptide-binding cleft and the diversity of peptides bound by the HLA-C molecules. Together with a phylogenetic analyses, these results highlight the diversity and long-term balancing selection of regulatory factors that modulate HLA-C expression.